Walking Dissonance in Delhi: Intersections Among Daily Mobility, Environmental Exposures, and Wellbeing - Mondschein, Andrew (University of Virginia, 2020)
Despite the rapid pace of change and investment, most Delhi residents continue to struggle to get where they need to go, often depending on simply walking to get where they need to go. During travel, residents are directly exposed to the urban environment, with its air pollution, noise, and natural and built features that vary significantly in their quality and maintenance. How these exposures affect residents, both in how its shapes their travel and its impact on personal wellbeing, remain little investigated or understood. In order to address that gap in both scholarship and local knowledge, in 2019 we conducted a survey in two Delhi neighborhoods to better understand intersections among how people travel, perceptions of the urban environment, and effects on personal wellbeing. This survey of one thousand adults focuses on peripheral neighborhoods – Bhalswa Dairy and Batla House – with primarily low-income populations that have traditionally received little attention or investment from authorities. The survey results show that for residents of these neighborhoods, perceptions of low environmental quality are wrapped up with a perception of poor walking conditions that are nevertheless is an unavoidable facet of daily life for most residents. I introduce the concept of “walking dissonance,” which occurs when individuals must walk frequently despite negative perceptions of walkability. The findings underscore that the development of a just, equitable transportation system in Delhi cannot just focus on investments in large-scale, regional networks, but need to address the effects of the environment on the fine-scaled, (in)human spaces of local mobility.
Original submission date: 2020-12-09T18:48:48Z